FOTO KEBUDAYAAN PADA KARYA TRADISI SAEYYANG PATTUQDUQ DI MANDAR KARYA MUHAMMAD RIDWAN ALIMUDDIN (ANALISIS SEMIOTIKA CHARLES SANDERS PEIRCE) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This study aims to determine the meaning contained in cultural photographs in the Saeyyang Pattuqduq tradition using Charles Sanders Peirce's semiotic analysis. The objects of this study are four series of photographs of the Saeyyang Pattuqduq tradition by Muhammad Ridwan Alimuddin including (ritual Totammaq (people who read the Koran), Saeyyang Pattuqduq (Horse Dancer), Parrawana (tambourine beater) and pakkalindaqdaq (Syring Poetry). This study uses a qualitative approach with text analysis methods through the semiotic analysis of Charles Sanders Peirce's semiotic model. Data collection by document analysis. The data analysis technique in this study is to clarify a sign using the types of signs, namely icons, indexes, and symbols. The results of this study indicate that the universal meaning in the four series of cultural photos in the Saeyyang Pattuqduq tradition by Muhammad Ridwan Alimuddin shows that it is not only related to entertainment but there is love, hope, respect, and hospitality as the needs of every human being, when a human being negates or negates one of three, then lost his humanity. Because basically humans are created to love one another, have hope as a form of belief in the coming of something good, and respect as mutual respect for others.